LESSON STUDI SEBAGAI UPAYA MENINGKATKAN AKTIVITAS BELAJAR MAHASISWA - Darwanto Darwanto (Eksponen, 2018)
Improving the quality of education in Higher Education can be started by improving the quality of lecturers in teaching and professional behavior. One of the priority education issues is the quality of education, especially the quality of learning. From the various conditions and potentials, the efforts that can be made to improve the quality of learning in Higher Education is to develop student oriented learning and facilitate it in learning. One of the models of educator profession development through collaborative and sustainable learning is Lesson Study. Through the stages in the lesson design can enhance student learning activities.